Changes in Lipid biomarker related to trauma severity in intertrochanteric fracture patients: Lipid biomarkers and trauma severity in fractures - Chen, Yang; Ye, Gang; Porter, Daniel Edwards; Chen, Xianyang; Wang, Wenjun; Li, Fei (Cellular and Molecular Biology, 2023)
This study aimed to identify whether there are elevations or declines in specific plasma lipids in intertrochanteric fracture (ITF) patients which might serve as potential biomarkers for assessing the severity of trauma, or therapeutic targets for controlling post-traumatic responses. Ten metal work removal patients were enrolled. Their preoperative blood samples served as the control group (C group). Their 24-hour postoperative blood samples served as the moderate trauma group (M group). The ITF group was composed of 12 intertrochanteric fracture patients. A total of 707 lipid species were identified from 32 plasma samples (10 controls, 10 moderate trauma and 12 ITF samples). We first identified 31 lipids that were elevated and 6 lipids that were decreased in the more severe trauma group in aged patients, with an especially strong relationship among 14 lipids that are candidates as markers for trauma severity evaluation. Fourteen lipids were identified as potential markers of bone trauma. The definition of important lipids in trauma may not only provide guidance for the formulation of optimum ITF operation time, but may also have importance in other traumatic models, and in further understanding the components of the systemic inflammatory response for new drug targets.